2023
DOI: 10.1177/02683962221114408
|View full text |Cite
|
Sign up to set email alerts
|

To regulate or not to regulate: unravelling institutional tussles around the regulation of algorithmic control of digital platforms

Abstract: Regulating how digital platforms use algorithms to determine and control content displayed to their users has become a controversial topic and an important societal challenge. Despite the acknowledgement of institutional tussles around regulation of algorithmic control, we lack research on how the development of regulation takes place. This research examines the process of institutional work by actors to develop regulation. We study two cases of algorithmic control regulation in Australia: one involving algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…The institutional landscape of the field can evolve as new actors take on important roles, or incumbents adapt by enacting new technologies or address new pressures from social media platforms and citizen demands. For instance, as in other information intensive fields, we may see algorithms more heavily determine information content (Kokshagina et al, 2023) related to emergencies and thus change the rules of the game (Constantiou & Kallinikos, 2015; Schildt, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The institutional landscape of the field can evolve as new actors take on important roles, or incumbents adapt by enacting new technologies or address new pressures from social media platforms and citizen demands. For instance, as in other information intensive fields, we may see algorithms more heavily determine information content (Kokshagina et al, 2023) related to emergencies and thus change the rules of the game (Constantiou & Kallinikos, 2015; Schildt, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…(3) mechanisms such as risk assessment, compliance by-design, compliance reporting obligations, digital resilience, and the use of certification schemes to demonstrate compliance. While the financial industry is often in the cross-hairs with governments concerning regulatory principles and rules, it engages in what is called 'institutional tussles' to ensure a favourable regulatory climate for the industry (Karanasios et al, 2023;Colangelo et al, 2021).…”
Section: Unpacking the Complex Concept Of Regulationmentioning
confidence: 99%
“…Recently, as this special issue demonstrates, the growing dominance of digital platforms has given birth to novel risks which amplify the negative affordances of IT artefacts across most industries and society. Another area of concern highlighted in this special issue is the reliance on complex national and global digital infrastructures (DI) which pose novel risks to individuals, markets, and societies (Gleiss et al,2023;Henningsson and Eaton, 2023;Karanasios et al, 2023;Lindman et al, 2023;Schnurr et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The application of these three theories to grand challenges research (Besharov et al, 2019) led us (the organizers) to assume that the selected lenses might be combined fruitfully. Prior research beyond the theme of grand challenges and sustainability has demonstrated that combinations of selected lenses can enable scholars to develop insightful theories (Kokshagina et al, 2023; Krautzberger et al, 2021; Putnam et al, 2016).…”
Section: Introductionmentioning
confidence: 99%